Foreign Policy Making in Venezuelan Crisis: The Case of Nicolás Maduro’s Left- Wing Militaristic Cabinet in Venezuela’s Blockade Policy towards Brazilian Aids - Nauvarian, Demas (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
Venezuela has experienced a turmoil of economic crisis since 2014 under the administration of President Nicolás Maduro. This crisis has been spilling towards social and political issues, with one being the emergence of opposition group led by Juan Guaidó. This crisis, at first, has invited sympathy from various international actors, both states and non-states, one of them being Brazil. However, in February 2019, President Maduro decided to fully-blockade Venezuela-Brazil borders for any human or goods movement. This paper aims to analyze the presence of President Maduro’s cabinet towards Brazil borders blockade in Venezuelan Crisis in 2019. This paper utilizes qualitative social science methodology by analyzing primary and secondary data. By using the groupthink paradigm in foreign policy analysis, this paper argues that there is a position convergence between the members of the cabinet with the background of: (1) the dominance of nationalist military group loyal to President Maduro; (2) the same ideology of left-wing political spectrum. This paper also argues that beside the two internal factors above, the external factors of regional and global tension towards Venezuela also create an isolation as an element of stress towards this government. This paper concludes that the combination of the three factors above become the main factors that formulated the blockade policy.